1987
DOI: 10.1007/bf02343219
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged indomethacin treatment in preterm infants with symptomatic patent ductus arteriosus: efficacy, drug level monitoring, and patient selection

Abstract: Indomethacin treatment for 1 week monitored by drug level determinations was evaluated in 32 preterm infants with symptomatic patent ductus arteriosus (sPDA). Inter- and intra-individual indomethacin dispositions varied considerably with the need for marked dosage adjustments to maintain the drug level within the proposed therapeutic range. The overall success rate of this prolonged treatment was 63%. There were no significant differences between the groups of responders (n = 20), relapsers (n = 5) and non-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Several older studies have suggested that a longer initial course of indomethacin therapy may be more effective in producing permanent ductus closure than the standard 3-dose course. [7][8][9] In contrast, more recent studies have found that a longer course of indomethacin is no more effective than the standard 3-dose course in producing permanent closure. 18 -23 We hypothesize that the different outcomes among these studies may be attributable to differences in the degree of ductus constriction during the standard 3-dose course of indomethacin.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Several older studies have suggested that a longer initial course of indomethacin therapy may be more effective in producing permanent ductus closure than the standard 3-dose course. [7][8][9] In contrast, more recent studies have found that a longer course of indomethacin is no more effective than the standard 3-dose course in producing permanent closure. 18 -23 We hypothesize that the different outcomes among these studies may be attributable to differences in the degree of ductus constriction during the standard 3-dose course of indomethacin.…”
Section: Discussionmentioning
confidence: 95%
“…1 Numerous factors have been shown to play a role in both spontaneous and indomethacin-induced ductus closure: gestational age, exposure to antenatal steroids, presence of respiratory distress, fluid intake, postnatal age at the time of treatment, and duration of indomethacin treatment. 1,2,[7][8][9][10][11][12][13][14] However, at this point in time, no studies have determined which factors predict permanent ductus closure when Doppler-detectable luminal flow is still present after the standard 3-dose course of indomethacin.…”
mentioning
confidence: 99%
“…It is known that indomethacin causes a decrease in cerebral, renal and mesenteric blood ow velocity (7)(8)(9)(10), probably caused by vasoconstriction, which will subsequently reduce organ perfusion. The frequently observed side effects of indomethacin treatment, such as impairment of renal function and gastrointestinal problems (11)(12)(13) have often been related to the changes in organ blood ow. Reduction of the changes in organ blood ow might therefore reduce the side effects of indomethacin treatment.…”
mentioning
confidence: 99%
“…Seyberth et al [19] gave indomethacin over a 7-day period without evidence of increased toxicity; however, there was no control population with a shorter dosage interval. A second study from the same group again indicated efficacy but was focused more on drug monitoring and there was again no control group [7]. This prolongation of therapy may also prevent ductal reopening.…”
Section: Introductionmentioning
confidence: 91%